4, 4'-dimethoxychalcone increases resistance of mouse oocytes to postovulatory aging in vitro. Issue 3 (March 2022) - Liu, Lu; Huang, Jie; He, Anlan; Zhou, Shuai; Lu, Qianneng; Yu, Xiaoning; Bai, Xue; Li, Mingrui; Huo, Ran
Abstract: Research question: Does 4, 4'-dimethoxychalcone (DMC), a natural antioxidant compound, effectively improve the quality of postovulatory ageing (POA) oocytes? Design: Freshly ovulated MII oocytes were cultured in 10-µM DMC for 12 h in vitro . Reactive oxygen species (ROS) production, apoptosis rate, mitochondrial distribution, formation of the actin cap, and fertilization and development potential of POA oocytes, were studied. The change of autophagy level was detected, and the autophagy inhibitor 3-methyladenine (3-MA) was used to establish the relationship between DMC and autophagy. Results: DMC supplementation eliminated the accumulated ROS ( P < 0.0001) and ROS dependent 4 hydroxynonenal products ( P = 0.0399), and decreased apoptosis ( P = 0.0033), reduced abnormal mitochondrion distribution ( P = 0.0280), improved mitochondrial membrane potential ( P = 0.0135) and restored the formation of the actin cap ( P = 0.0487), thus improving fertilization ability ( P = 0.0156) and developmental potential ( P = 0.0130) in POA oocytes. The role autophagy plays in the effects of DMC supplementation was investigated. The immunofluorescence results showed that POA leads to the accumulation of SQSTM1/p62 ( P = 0.0083) but DMC supplementation could eliminate this ( P < 0.0001). The western blot result of p62 protein was similar to the immunofluorescence results of the POA group ( P = 0.0441) and DMC supplementation group ( P = 0.0154). After inhibiting autophagy by 3-MA, the DMC supplementation group could no longer eliminate the accumulation of ROS ( P = 0.1704). Conclusions: DMC supplementation activates autophagy to protect oocytes from postovulatory ageing. This approach can feasibly improve the reproductive outcome of ART.